Last days of man [videorecording (DVD)] : top 10 doomsday scenarios - Sjöström, Magnus
A scientific examination of the top ten disasters that have the capacity to annihilate the human race-and it's not just the usual threats from nuclear weapons, climate change, and meteorite impacts. There are a number of lesser-known but much more probable risks to humankind-threats that humanity has created for itself.